ANALISIS KESULITAN GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA: MINIMNYA PELATIHAN DAN DAMPAKNYA TERHADAP PEMBELAJARAN SOAL CERITA MATEMATIKA DI UPT SDN 001 SALO - Rizki Ananda; Fathur Rahman Sadaat; Irsyad Al-Faruqi; Elma Salpina; Meysi Liliantika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The independent learning curriculum has been implemented in the third year, the first year of grades I and IV, the second year of grades II and V, and the third year of grades III and VI have been completed using the Independent Curriculum. This Independent Curriculum is very flexible to implement. The purpose of the study was to determine the form of teacher difficulties in implementing the Independent Curriculum at UPT SDN 001 Salo. The method used in this study is a descriptive narrative method with a qualitative approach. The results of this study are that there are difficulties in implementing the Independent Curriculum felt by teachers such as teacher training and readiness which are still lacking where teacher training is one cluster and then carried out independently from YouTube, many learning models are not yet known and understood by teachers so that teachers are confused about using learning models when implementing the Independent Curriculum.